Changes in symptoms during urologic chronic pelvic pain syndrome symptom flares: Findings from one site of the MAPP Research Network. Issue 2 (23rd November 2013) - Sutcliffe, Siobhan; Colditz, Graham A.; Pakpahan, Ratna; Bradley, Catherine S.; Goodman, Melody S.; Andriole, Gerald L.; Lai, H. Henry
Abstract Aims To provide the first description and quantification of symptom changes during interstitial cystitis/bladder pain syndrome and chronic prostatitis/chronic pelvic pain syndrome symptom exacerbations ("flares"). Methods Participants at one site of the Trans‐Multidisciplinary Approaches to the study of chronic Pelvic Pain Epidemiology and Phenotyping Study completed two 10‐day diaries over the 1‐year study follow‐up period, one at baseline and one during their first flare (if not at baseline). On each day of the diary, participants reported whether they were currently experiencing a flare, defined as "symptoms that are much worse than usual" for at least 1 day, and their levels of urination‐related pain, pelvic pain, urgency, and frequency on a scale of 0–10. Linear mixed models were used to calculate mean changes in symptoms between non‐flare and flare days from the same participant. Results Eighteen of 27 women and 9 of 29 men reported at least one flare during follow‐up, for a total of 281 non‐flare and 210 flare days. Of these participants, 44.4% reported one flare, 29.6% reported two flares, and 25.9% reported ≥3 flares over the combined 20‐day diary observation period, with reported flares ranging in duration from 1 day to >2 weeks. During these flares, each of the main symptoms worsened significantly by a mean of at least two points and total symptoms worsened by a mean of 11 points for both sexes (all P ≤ 0.01). Conclusions Flares are common and correspond to a global worsening of urologic and pelvic pain symptoms. Neurourol. Urodynam. 34:188–195, 2015. © 2013 Wiley Periodicals, Inc.